2017
DOI: 10.16956/jes.2017.17.4.168
|View full text |Cite
|
Sign up to set email alerts
|

Percentage Decline of Parathyroid Hormone Level is a Predictor for Post-thyroidectomy Symptomatic Hypocalcemia

Abstract: Purpose: Postoperative hypocalcemia is one of the most common complications after thyroid surgery. However, the predictive efficacy of parathyroid hormone (PTH) level was still controversial. We investigated the cut-off value of perioperative PTH level for postoperative hypocalcemia after total thyroidectomy. Methods: Four hundred eighty-two patients performed total thyroidectomy from January 2015 to December 2016 were enrolled. Demographics, operative variables and the development of symptomatic hypocalcemia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…This means that vitamin D3 injection might prevent TH, especially in patients with postoperatively borderline-low PTH levels. Jung et al reported that decline of postoperative PTH levels can be used as a predictive factor for TH [ 33 ]. Vitamin D3 injection may be helpful in situations where PTH levels may be decreased postoperatively, such as in thyroiditis, extensive lymph nodes metastasis at level VI, Graves' disease, history of previous neck operation, and extensive surgical resection.…”
Section: Discussionmentioning
confidence: 99%
“…This means that vitamin D3 injection might prevent TH, especially in patients with postoperatively borderline-low PTH levels. Jung et al reported that decline of postoperative PTH levels can be used as a predictive factor for TH [ 33 ]. Vitamin D3 injection may be helpful in situations where PTH levels may be decreased postoperatively, such as in thyroiditis, extensive lymph nodes metastasis at level VI, Graves' disease, history of previous neck operation, and extensive surgical resection.…”
Section: Discussionmentioning
confidence: 99%